Positive Correlation of Social Support and Academic Flow in Biology Students: Korelasi Positif antara Dukungan Sosial dan Aliran Akademik pada Mahasiswa Biologi - Nofi Lina; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Academic engagement is crucial for maintaining concentration and optimizing student learning processes. Specific Background: Observations among Biology students at the University of Lampung indicated decreased classroom focus, frequent gadget use during lectures, and low motivation in completing practicum reports. Knowledge Gap: Empirical studies examining the relationship between social support and academic flow among Biology undergraduate students remain limited. Aims: This study investigates the relationship between social support and academic flow among fourth-semester Biology students at the Faculty of Mathematics and Natural Sciences, University of Lampung. Results: Using a correlational quantitative design with Likert-scale psychological instruments and SPSS 25.0 analysis, the findings showed a significant positive relationship between social support and academic flow, with a correlation coefficient of r = 0.265 and a significance value of 0.019 (<0.05). Novelty: This study presents quantitative evidence specifically examining academic flow in Biology students through standardized measurement of social support variables. Implications: The findings indicate that strengthening interpersonal support systems is associated with improved student engagement and concentration during academic activities, providing considerations for educational stakeholders in supporting learning experiences. Highlights: Interpersonal Assistance Is Statistically Associated With Optimal Learning Immersion. Quantitative Measurement Confirms Moderate Relational Strength Between Examined Variables. Learner Engagement Challenges Relate to Reduced Practicum Completion Motivation and Lecture Focus. Keywords: Academic Flow, Social Support, Undergraduate Learning Engagement, Higher Education Psychology, Student Concentration